1996
DOI: 10.1063/1.116477
|View full text |Cite
|
Sign up to set email alerts
|

Transverse mode dynamics in vertical cavity surface emitting lasers excited by fast electrical pulses

Abstract: We report measurements of the transient multimode dynamics of vertical cavity surface emitting lasers excited by short ͑100-200 ps rise times, 1 ns duration͒ electrical pulses. Fast changes on the spatial distribution of the output power and strong mode competition are observed. Numerical simulations show that the observed dynamics are due to the partial overlap of the different transverse modes through spatial hole burning. © 1996 American Institute of Physics. ͓S0003-6951͑96͒04505-0͔Recent advances in semico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 4 publications
3
24
2
Order By: Relevance
“…Modeling results concerning the turn-on behavior also indicate that the laser starts to emit in low order modes due to their lower threshold, compared with higher order modes [15]. Spectrally, however, not spatially resolved experiments performed by Buccafusca et al [7], [8], [19] agree very well with the observed behavior. The set of excited modes during the first relaxation oscillation peak depends on pumping conditions, and there is little change in the relative intensity increase among the modes, indicating that during this time the threshold behavior of each mode dominates the evolution of the near-field intensity [8].…”
Section: Analysis Of the Underlying Mechanismssupporting
confidence: 75%
See 1 more Smart Citation
“…Modeling results concerning the turn-on behavior also indicate that the laser starts to emit in low order modes due to their lower threshold, compared with higher order modes [15]. Spectrally, however, not spatially resolved experiments performed by Buccafusca et al [7], [8], [19] agree very well with the observed behavior. The set of excited modes during the first relaxation oscillation peak depends on pumping conditions, and there is little change in the relative intensity increase among the modes, indicating that during this time the threshold behavior of each mode dominates the evolution of the near-field intensity [8].…”
Section: Analysis Of the Underlying Mechanismssupporting
confidence: 75%
“…The observation, analysis, and understanding of the spatio-temporal dynamics on picosecond timescales, associated with the multiple transverse modes, is thus not only promising for device optimization, but also allows us to gain physical insight into the underlying mechanisms and laser-matter interaction. Up to now, only spatially integrated [7], [8] and one-dimensional cuts [9] of the time-resolved dynamics of the near-field intensity exist, precluding investigations of the dynamics of the full 2-D-spatial interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The carrier density slope must vanish at the origin when there is azimuthal symmetry and, when the injection current is supplied in a region near the center of the device, a vanishing slope of the carrier density can be assumed at the boundary of the active region [22]. The resulting time evolution of the carrier density components is given by (9) and the time evolution of the optical intensities by (10) In the above equations, new parameters appear (11) which accounts for the driving current of the component, resulting from the overlapping with the current density profile.…”
Section: Modelmentioning
confidence: 99%
“…On the other hand, it is known that spatial hole burning (SHB) and carrier diffusion play key roles in transverse mode selection and, in turn, these processes depend upon the laser drive current [8], [9]. Experiments have been carried out recently showing such effects [10]. Consequently, the excitation of transverse modes when the laser is subject to large excursions in the bias current will be strongly influenced by SHB effects.…”
mentioning
confidence: 99%
“…The mode-locked state may be achieved after a certain transient [1,2], by different approaches: in fibers just a small Kerr nonlinearity is needed to obtain mode locking [3], while in laser cavities nonlinear coupling may be obtained by active or passive modulation [4]. The ML is modeled by a nonlinear Schrodinger equation whose stable solutions are solitonlike.…”
Section: Introductionmentioning
confidence: 99%